Undocumented objects: The collection Cavalcanti at Museum Volkenkunde, Leiden. Issue 1 (2nd January 2019) - Santos, Rita de Cássia Melo
ABSTRACT: The Marquesa de Cavalcanti Collection kept at the Volkenkunde Museum, in Leiden, the Netherlands, is one of the oldest records of the existence of Brazilian objects in this museum. It is part of a broader collection created for the Brazilian Anthropological Exhibition, held in 1882, and for the Universal Exhibition in Paris, held in 1889. The main focus of this article is on the itineraries of this collection from its first exhibitions in Brazil and Paris to the Volkenkunde collection in Leiden. Despite the challenge posed by lack of documentation to understand the 'social life' of objects, we believe that the investigation of the itineraries of collections and the analysis of different social relations inscribed in objects may provide a key to understanding the history of ethnographic and archaeological collections. This article analyses how collections connected colonial regions to metropolitan areas in the second half of the nineteenth century, in the particular case of Brazil, Paris, and the Netherlands. It further discusses the role of women in the production of archaeological and ethnographic collections and, consequently, their place in the production of anthropological and archaeological knowledge.